Diamine derivative of a ruthenium(II)-polypyridyl complex for chemodosimetric detection of nitrite ion in aqueous solution - Ghosh, Amrita; Das, Priyadip; Saha, Sukdeb; Banerjee, Tanmay; Bhatt, Harshad B.; Das, Amitava (Inorganica Chimica Acta, 2011)
Nitrite is quite an abundant anion in the environment. It, however, becomes toxic to human life, as well as aquatic animals when present above the permissible concentration level. We have reported here a Ru(II)-polypyridyl-based complex (1) for chemodosimetric detection of nitrite ion in aqueous solution. Formation of the new triazole based complex, generated by reaction of 1 and N2O3, is ascertained by comparing its properties with a presynthesised triazole complex.

Solvent-dependent aggregation behavior of a new Ru(ii)-polypyridyl based metallosurfactant - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chemical Communications, 2011)
Variation of the solvent polarity leads to the formation of vesicles and reverse vesicles of a newly synthesized amphiphilic Ru(II)-polypyridyl complex.

Urea/thiourea derivatives and Zn(II)-DPA complex as receptors for anionic recognition-a brief account - Das, Priyadip; Mahato, Prasenjit; Ghosh, Amrita; Mandal, Amal Kumar; Banerjee, Tanmay; Saha, Sukdeb; Das, Amitava (Journal of Chemical Sciences, 2011)
This review covers few examples of anion complexation chemistry, with a special focus on urea/thiourea-based receptors and Zn(II)-dipicolyl amine-based receptors. This article specially focuses on structural aspects of the receptors and the anions for obtaining the desire specificity along with an efficient receptor–anion interaction. Two types of receptors have been described in this brief account; first one being the strong hydrogen bond donor urea/thiourea derivatives, which binds the anionic analytes through hydrogen bonded interactions; while, the second type of receptors are coordination complexes, where the coordination of the anion to the metal centre. In both the cases the anion binding modulate the energy gap between the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) and thereby the spectroscopic response. Appropriate choice of the signalling unit may allow probing the anion binding phenomena through visual detection.

Interfacial and film formation behavior of photoactive Ru(ii)bipyridyl based metallosurfactants and a rare example of a monolayer based logic gate approach - Mahato, Prasenjit; Saha, Sukdeb; Choudhury, Sipra; Das, Amitava (Chempluschem, 2012)
Three derivatives of tris(bipyridyl)–ruthenium(II) complexes with different alkyl-chain lengths (nC18H37 (1), nC14H29 (2) and nC10H21 (3)) were synthesised. All these complexes behaved as an amphiphile and their surface properties were studied at the air–water interface by measuring surface pressure–area (Π–A) isotherms. The surface morphology of the resulting films at the air–water interface was also studied by using Brewster angle microscopy. Mean molecular areas of these complexes were measured from the Π–A isotherms, which were approximately 200 Å2, thereby indicating a parallel arrangement of the Ru–bipyridyl moiety of the complexes. Mono- and multilayer Langmuir–Blodgett (LB) films were formed on different solid surfaces with transfer ratios close to one. Similarities in the absorption and fluorescence spectra of these amphiphiles in solution as well as in LB films deposited on a quartz surface confirmed the successful transfer of these films onto the substrates. The latter provided information about the arrangements of metallosurfactant molecules within the LB films. The two-dimensional concentrations of these films were calculated from the Lambert–Beer law as well as from the Π–A isotherm, which confirmed regular and reproducible transfer of the complex monolayers from the air–water interface onto the quartz surface. The surface morphology of these films on various substrates was characterised by atomic force microscopy. Furthermore, by oxidising the monolayer of complex 3, a one-input sequential logic gate was constructed.

Interrupted PET coupled TBET process for the design of a specific receptor for Hg2+ and its intracellular detection in MCF7 cells - Saha, Sukdeb; Mahato, Prasenjit; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2012)
A new coumarin–rhodamine conjugate constitutes a unique example of the interrupted PET coupled TBET response for developing an imaging reagent for determining the intracellular distribution of Hg2+ in MCF7 cells exposed to [Hg2+] as low as 2 ppb.

Rare example of TICT based optical responses for the specific recognition of Cr3+ by a 2,2?:6?,2?-terpyridine derivative and demonstration of multiple logic operations - Mahato, Prasenjit; Saha, Sukdeb; Das, Amitava (Journal of Physical Chemistry C, 2012)
Chemosensor L showed a nonlinear fluorescence response on specific binding to Cr3+ ion in the presence of various alkali, alkaline-earth, transition, and lanthanide metal ions. A luminescence band with maxima at 512 nm for L was observed (λext = 330 nm) for a twisted intramolecular charge transfer (TICT) transition following antienergy gap law behavior. However, normal energy gap law behavior prevailed on formation of a new nonluminescent charge transfer complex, Mn+·L. For paramagnetic metal ions, paramagnetism induced luminescence quenching could have also contributed to this. A new switched on fluorescence response at λems of 356 nm (λext of 330 nm) was observed due to Franck–Condon charge transfer (FC-CT) transition only on the formation of a complex, (Cr3+)2·L. Spectral studies revealed a unique dynamic coordination behavior and migration of Cr3+ from the terpyridyl fragment to the NNMe2 center of L as a function of the varying concentration of another ion (Zn2+) and the subtle difference in the binding affinities of the terpyridyl moiety toward Cr3+ and Zn2+. Further, spectral responses of L toward Zn2+, different concentration of Cr3+, H+ and on subsequent addition of F– as different ionic inputs could be correlated well for demonstrating various basic and combinatorial circuits.

Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.

Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

Rhodamine-alginate conjugate as self-indicating gel beads for efficient detection and scavenging of Hg 2+ and Cr 3+ in aqueous media - Saha, Sukdeb; Chhatbar, Mahesh U.; Mahato, Prasenjit; Praveen, L.; Siddhanta, A. K.; Das, Amitava (Chemical Communications, 2012)
Effective extraction of Hg2+ and Cr3+ ions from aqueous media by novel rhodamine–alginate polymer-based highly fluorogenic, as well as colorimetric, chemosensor beads.

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

New chemodosimetric probe for the specific detection of Hg2+ in physiological condition and its utilisation for cell imaging studies - Saha, Sukdeb; Agarwalla, Hridesh; Gupta, Hariom; Baidya, Mithu; Suresh, E.; Ghosh, Sudip K.; Das, Amitava (Dalton Transactions, 2013)
A dithiane derivative of BODIPY is synthesized. This new reagent could be used for the specific and instantaneous detection of Hg2+ in physiological condition. This dithiane reagent reacts specifically with Hg2+ to regenerate the parent BODIPY-aldehyde with consequential change in visually detectable optical responses and this provides the possibility of using this reagent as a colorimetric probe or as a fluorescent biomarker/imaging reagent. Further, non-covalent interactions could be utilized for formation of an inclusion complex with biologically benign beta-cyclodextrin for enhancing its solubility in aqueous environment and this included adduct could be used as a fluorescent marker and imaging reagent for Hg2+. Uptake of Hg2+ ions in live HeLa cells, exposed to a solution having Hg2+ ion concentration as low as 2 ppb, could also be detected by confocal laser microscopic studies.

Self-assembly of modified rhodamine-6G with tri-block copolymer: unusual vesicles formation, pH sensing and dye release properties - Praveen, L.; Saha, Sukdeb; Jewrajka, Suresh K.; Das, Amitava (Journal of Materials Chemistry B, 2013)
A new rhodamine-6G derivative having a C18-alkyl chain self-assembles with an amphiphilic tri-block copolymer and forms stable vesicles in water or in water–ethanol (4 : 1, v/v) medium. The stability of the spirolactam form of the rhodamine-6G derivative in these vesicular structures, along with studies of controlled dye release and pH sensing are discussed. Transmission electron micrographs and DLS analyses confirm the formation of vesicular structures. Atomic force microscopy (AFM) images show that the self assembled tri-block copolymer-octadecyl rhodamine vesicles form near spherical nanostructures with a size ranging from 80 to 110 nm. Furthermore, the vesicular system is disassembled under acidic conditions, releasing the cargo which are an integral part of the vesicle. Dye-release studies showed that the release rates of the loaded dye in the vesicles could be well-controlled as a function of the media pH. These results offer an opportunity to use these nanovesicles as imaging reagents for probing media pH with their simultaneous use as nanocarriers for intracellular drug delivery.

Overview of the recent developments on Hg2+ recognition - Mahato, Prasenjit; Saha, Sukdeb; Das, Priyadip; Agarwalla, Hridesh; Das, Amitava (RSC Advances, 2014)
Adverse influences of mercury on living organisms are well known. Despite efforts from various regulatory agencies, the build-up of Hg2+ concentration in the environment is of serious concern. This necessitates the search for new and efficient reagents for recognition and detection of Hg2+ in environmental samples as well as for application in diagnostics. Among various detection processes adopted for designing such reagents, generally methodologies that allow associated changes in spectra properties are preferred for the obvious ease in the detection process. Significant changes in the electronic spectral pattern in the visible region of the spectrum also induce detectable changes in solution colour for naked-eye detection and are useful for developing reagents for in-field sample analysis with yes-no type binary responses. However, reagents that allow detection of Hg2+ with associated fluorescence on response are useful for detection of Hg2+ in environmental samples, as well as for use as an imaging reagent, for detection of cellular uptake. High spin-orbit coupling constant for Hg2+ along with its high solvation energy in aqueous medium poses a challenge in developing efficient reagents with fluorescence on response that work in aqueous medium/physiological condition. To get around this problem, several methodologies, like conversion of rhodamine derivative spirolactam to strongly fluorescent xanthenes that form on binding to Hg2+, chemodosimetric reaction for generation of a new luminescent derivative, have been adopted. Apart from these, modified charge transfer processes on binding to Hg2+ have also been utilized for designing reagents for optical detection of Hg2+. Immobilization of such reagents on solid surfaces also led to the development of self-indicating Hg2+ ion scavengers. All such examples are discussed in the present review.

Rapid conductometric sensor for the analysis of cyanide using imidazole based receptor - Paul, Anirban; Perween, Mosarrat; Saha, Sukdeb; Srivastava, Divesh N.; Das, Amitava (Physical Chemistry Chemical Physics, 2015)
A specific and efficient hydrogen bonding interaction between cyanide and the HN-H [imidazole] in an aqueous medium has been utilized for the selective recognition of cyanide under physiological conditions. The possibility of utilizing such an interaction for developing any practical device for the specific detection of cyanide in an aqueous environment has not been explored to date. We now report a simple dip and read conductometric sensor for cyanide ions using a tailored electrode in aqueous media. The purpose built reagent, 2-phenyl-1H-anthra-[2,3-d]-immidazole-5,10 dione was immobilized in a polyaniline matrix to fabricate this conductometric device. The homogeneous immobilization of the receptor in polyaniline was confirmed by FT-IR mapping. The proposed transduction mechanism is charge neutralization on the polyaniline moiety, which ultimately inhibits the protonation resulting in a decrease in the conductance of polyaniline. The sensor response was measured in three ranges of cyanide concentration (10(-10) M to 10(-8) M; 10(-8) M to 10(-6) M and 10(-6) M to 10(-3) M). Whereas the device is found insensitive in the first range, it acts as a detector in the second range and as a proportional sensor in the third range. The minimum detection limit of this device was found to be 10 nmol L-1 (2.6 ppt), which is significantly less than the WHO guideline values. The responses have been investigated under various conditions such as different pH and the electrochemical state of the polymer. The current device has been found to be better close to neutral pH and at a 400 mV vs. Ag/AgCl potential. The reproducibility and repeatability of the sensor was investigated and interference studies were performed.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).